PENINGKATAN MOTIVASI BELAJAR IPA MELALUI METODE PEMBELAJARAN QUANTUM TEACHING BAGI SISWA KELAS IV - Fauzatul Ma’rufah Rohmanurmeta (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2015)
At the elementary school level, sains learning still monotonous anduninteresting because elementary school system with classroom teachers to makethe teachers have difficulty in using the right strategy. Teachers are required toachieve the target material that is quite a lot and should be comleted in eachsemester.This situation resulted in the lack of attention of student in the process oflearning activities so that a low student motivation. Under these conditions, thepurpose of this research is to improve students motivation through quantumteaching method of learning process in the fourth grade students of SDN 02 WatesDistric jenangan, Ponorogo.This research is a classroom action research (PTK),which consists of the first cycle and the second cycle. The study subjects werestudents of class 4 SDN 02 Wates wich consist 11 students. Collecting data in thisstudy using a questionnaire to determine students motivation, and the observationsheet in the form of check list to determine the activity of students. Before heldresearch student motivation is low. Then after research showed that motivation ofstudents of cycle 1 45,5% and cycle II 82% increased 36,5%. Interpretation ofstudent learning to learning in sycle 1 is 36% and cycle II increased to 82%.Student activity in I cycle was 27,3% and in the II cycle increased to 81,8%. Theresult showed that the use of quantum teaching methods can improve studentsmotivation in learning sains SDN 02 wates.